Respuesta :
Answer:
[tex]{ \tt{y = {x}^{2}(x + 1) }} \\ \\ { \tt{ \frac{dy}{dx} = (2x)(x + 1) + ( {x}^{2})(1) }} \\ \\ { \tt{ \frac{dy}{dx} = 2 {x}^{2} + 2x + {x}^{2} }} \\ \\ { \tt{ \frac{dy}{dx} = 3 {x}^{2} + 2x }} \\ \\ { \boxed{ \tt{ \frac{dy}{dx} = x(3x + 2) }}}[/tex]
Answer:
[tex]{ tt{y = {x}^{2}(x + 1) }} \\ \\ { \tt{ \frac{dy}{dx} = (2x)(x + 1) + ( {x}^{2})(1) }} \\ \\ { tt{ \frac{dy}{dx} = 2 {x}^{2} + 2x + {x}^{2} }} \\ \\ { \tt{ \fac{dy}{dx} = 3 {x}^{2} + 2 }} \\ \\ { \boxed{ \tt{ \frc{dy}{dx} = x(3x + 2) }}}[/tex]